The interactions between the soil yeast Papiliotrema laurentii and two Western Cape crops, wheat (Triticum aestivum L.) and rooibos (Aspalathus linearis (Burm. F.) R. Dahlgren) - Van den Heever, Christiaan Frederick (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.